Loss of peri-Wolffian duct stromal Frs2α expression in mice leads to abnormal ureteric bud induction and vesicoureteral reflux - Narla, Deepti (Pediatr Res, 2017)
BACKGROUND: Fibroblast growth factor receptor 2 (Fgfr2) deletion from murine peri-Wolffian duct stroma (ST) results in aberrant ureteric bud induction, abnormal ureteral insertion into the bladder, and high rates of vesicoureteral reflux (VUR). It is unclear which receptor docking protein(s) is/are responsible for Fgfr2 actions in these tissues. We investigated whether the docking protein, fibroblast receptor substrate 2α (Frs2α), had roles in peri-Wolffian duct stroma similar to Fgfr2. METHODS: We conditionally deleted Frs2α in per-Wolffian duct stroma with a Tbx18cre mouse line (Frs2α(ST−/−)). We assessed for ureteric induction defects and alterations in downstream targets mediating defects. We performed euthanized cystograms and assessed ureter-bladder junctions via three dimensional (3D) reconstructions. RESULTS: Embryonic day (E) 11.5 Frs2α(ST−/−) embryos had many displaced ureteric bud induction sites versus controls. E11.0 Frs2α(ST−/−) embryos had decreased Bmp4 expression and signaling, which can cause abnormal ureteric bud induction. Postnatal day 1 (P1) and P30 Frs2α(ST−/−) mice had higher VUR rates and grades versus controls. Mutant refluxing ureters inserted improperly into the bladder and had shortened intravesicular tunnels versus controls: CONCLUSIONS: Frs2α(ST−/−) have aberrant ureteric induction sites, improper ureteral insertion, shortened intravesicular lengths and VUR. Induction site defects appear secondary to reduced Bmp4 expression, similar to Fgfr2 mutants.